1955
DOI: 10.1161/01.cir.12.3.391
|View full text |Cite
|
Sign up to set email alerts
|

QS- and QR-Pattern in Leads V 3 and V 4 in Absence of Myocardial Infarction: Electrocardiographic and Vectorcardiographic Study

Abstract: A QS or QR pattern in the absence of myocardial infarction is frequently present in lead V3 and occasionally in lead V4. Exploration by means of multiple chest and abdominal unipolar leads and vectorcardiograms revealed that in almost all such cases, the vector of the initial portions of the QRS complex is directed downwards. Accordingly, in the absence of infarction, patients presenting this pattern almost invariably showed an initial R wave in the leads recorded from positions below the standard level of V3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1957
1957
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Superior displacement of the V 1 and V 2 electrodes will often result in rSrЈ complexes with T-wave inversion, resembling the complex in lead aVR. It also has been shown that in patients with low diaphragm position, as in obstructive pulmonary disease (88,89), V 3 and V 4 may be located above the ventricular boundaries and record negative deflections that simulate anterior infarction. Another common error is inferior placement of V 5 and V 6 , in the sixth intercostal space or even lower, which can alter amplitudes used in the diagnosis of ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Superior displacement of the V 1 and V 2 electrodes will often result in rSrЈ complexes with T-wave inversion, resembling the complex in lead aVR. It also has been shown that in patients with low diaphragm position, as in obstructive pulmonary disease (88,89), V 3 and V 4 may be located above the ventricular boundaries and record negative deflections that simulate anterior infarction. Another common error is inferior placement of V 5 and V 6 , in the sixth intercostal space or even lower, which can alter amplitudes used in the diagnosis of ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, despite standardization of their locations since the late 1930s, precordial leads V1 through V6 are still often subject to erroneous and inconsistent placement on the chest (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Such lapses in procedural adherence can lead not only to altered R-wave amplitude, but also false ECG diagnoses, most significantly ''ischemia'' (T-wave inversion, or ST-segment shifts) and ''infarction'' (Q waves or QS complexes), and additionally, ''Brugada syndrome'' (5,8,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). These misdiagnoses are far from trivial in that they can prolong evaluation time in the emergency department (ED) (and, thereby, contribute to the crowding problem); cause postponement of previously scheduled surgical procedures; lead to unnecessary non-invasive (and perhaps even invasive) diagnostic cardiac tests; prompt treatments that are potentially risky (e.g., intravenous antithrombotic or antiplatelet therapy) or expensive; and possibly raise a red flag if the patient applies for employment or life insurance (22,24).…”
Section: Introductionmentioning
confidence: 99%
“…Right precordial electrodes V1 and V2-which are supposed to be placed parasternally at the fourth intercostal space (ICS)-are particularly prone to being malpositioned superiorly (i.e., in a cranial direction) on the chest, possibly causing registration of T-wave inversions or QS complexes (6,12,(15)(16)(17)(18)(19)(20)(21)(22). Although such waveforms are part of the physiologic adult ECG morphologic spectrum in V1, their appearance in V2 (or in both V1 and V2) is usually considered abnormal, suggesting ischemia or infarction localized, by common convention, to the interventricular septum (albeit an anatomic oversimplification) (20,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…1 Septal, or midseptal infarction is an ECG diagnosis that has been used. 10 In the absence of incomplete or complete left bundle branch block (LBBB), other possible causes of QS deflections in leads V 1 -V 2 include improper precordial lead placement, 11,12 left ventricular hypertrophy (LVH), 11,13,14 unusual chest conformation, 12 congenital anomalies associated with ventricular inversion or dextrocardia, 15 emphysema, 13 and an intraventricular conduction defect involving the median or septal fibers of the left bundle branch (left septal fascicular block). 2,5−9 The latter, when due to infarction, indicate involvement of the anterior wall or apex of the left ventricle.…”
mentioning
confidence: 99%